Hammer: the tilt of the orbit - best strategies for both beginning and experienced throwers - Strelnitski, V. (Techniques Magazine, 2020)
This article was inspired by several discussions between the author and Yuri Sedykh, widely recognized (certainly by the author) as the best ever technician in hammer throing. Yuri insisted that for throwers with limited experience, entry should be "flat," a steep first orbit manageable only by mature throwers. Thinking about the physical rationale for this recommentation and how it can be combined with Yuri's other recommendations, such as to always keep the low point of the hammer "low" (close to the ground), I did some research, whose results are presented here. It was difficult to avoid some mathematics in the presentation of the results. The readers, who are not interested in formal arguments can limit themselves with Sections 1, 2, 5, and 6.